The Theoretical Approaches to Defining the Essence of the Notion of «Social Management» (Economic journal of Lesya Ukrainka Volyn National University, 2016)
Thus, based on the study of sources of scientific literature concluded that the interpretation of the term «social management» is quite diverse. It should be noted that the interpretation is radically different, as some scientists believe that the sphere of influence of social management is a social and others – economic. Also during the investigation it was determined that the scientists have not formed approaches to the interpretation of the essence of the concept of «social management». Therefore, using a number of general scientific and special methods of research, was allocated two approaches: theoretical and processes. Based on generalization and systematization main features of the investigated concept formulated by the author's definition, which, unlike existing in a particular approach that takes into account all aspects of the interpretation of the concept.
Keywords: social management, social management, management of social development of organization, theoretical approach, process approach